Recent ring distortion reactions for diversifying complex natural products. Issue 10 (16th August 2022) - Li, Yu; Cheng, Shihao; Tian, Yun; Zhang, Yanan; Zhao, Yu
Abstract : The ring distortion reactions recently used in complexity-to-diversity and pseudo natural product strategies for diversifying complex natural products have been overviewed. Abstract : Covering: 2013–2022. Chemical diversification of natural products is an efficient way to generate natural product-like compounds for modern drug discovery programs. Utilizing ring-distortion reactions for diversifying natural products would directly alter the core ring systems of small molecules and lead to the production of structurally complex and diverse compounds for high-throughput screening. We review the ring distortion reactions recently used in complexity-to-diversity (CtD) and pseudo natural products (pseudo-NPs) strategies for diversifying complex natural products. The core ring structures of natural products are altered via ring expansion, ring cleavage, ring edge-fusion, ring spiro-fusion, ring rearrangement, and ring contraction. These reactions can rapidly provide natural product-like collections with properties suitable for a wide variety of biological and medicinal applications. The challenges and limitations of current ring distortion reactions are critically assessed, and avenues for future improvements of this rapidly expanding field are discussed. We also provide a toolbox for chemists for the application of ring distortion reactions to access natural product-like molecules.